A formação de leitores na área de língua portuguesa na BNCC: orientações para o trabalho com a prática da leitura no 1º e 2º anos do Ensino Fundamental - Silva, Cíntya Gercilane Oliveira da (2023)
The present study sought to analyze the guidelines that the National Common Curricular Base (BNCC) brings in the Portuguese Language area for working with the practice of reading in the 1st and 2nd grade classes of Elementary School. Therefore, the general objective of this research is to investigate which reader training proposal is present in the Portuguese language BNCC for the 1st and 2nd grade classes of Elementary School. Thus, we established the following specific objectives: to identify and analyze the objects of knowledge and skills proposed for working with reading in the 1st and 2nd years of Elementary School in the Portuguese language area at BNCC; check BNCC guidelines/suggestions for teaching practice regarding the formation of readers in the 1st and 2nd years of Elementary School in the Portuguese language area. The documental research, which seeks to analyze the BNCC, and which performs an interpretative analysis of the data, was developed in three stages: (i) pre-analysis, (ii) organization of the material and (iii) treatment or analysis of the data. As for the theoretical foundation, the research dialogues with the studies of Manguel (2001), Freire (1997), Lajolo (1996), Cavalcanti (2002), Lévy (1993), Rojo (2015), among others. We found that the document emphasizes word decoding integrated with other reading skills, such as comprehension, interpretation and reflection on texts. Reading is not just about decoding, but also about understanding the meaning of texts and the ability to relate them to previous knowledge and personal experiences, using textual genres that children can have contact with on a daily basis, especially the most common ones. , such as lists, agendas, calendars, notices, invitations, recipes, assembly instructions and the like. We also found that there are certain suggestions, even if not detailed, as to what to work on and how to work on the skills, depending on the specificities of each class. However, it is up to the educator to define what best suits their class and reality in question.